The Value and Disvalue of Consciousness. (16th September 2016) - GLANNON, WALTER
Abstract: Consciousness defines us as persons. It allows us to have both pleasurable and painful experiences. I present four neurological conditions in the clinical setting to explore how consciousness can be beneficial or harmful to patients: intraoperative awareness, prolonged disorders of consciousness, locked-in syndrome, and the effects of narcotics and sedation on terminally ill patients. The ethical significance of consciousness for patients in these conditions depends on two factors: the content of one's experience and whether one can report this content to others. I argue that the value or disvalue of phenomenal consciousness, what it is like to be aware, may depend on its relation to access consciousness, the ability to report or communicate the content of awareness. Phenomenal consciousness can have disvalue when one wants or expects to be unconscious. It can also have disvalue in the absence of access consciousness because it can allow the patient to experience pain and suffer. Technology that enabled neurologically compromised patients to reliably communicate their experience and wishes could benefit and prevent harm to them. More generally, the neurological conditions I discuss raise the question of when and in what respects consciousness is preferable to unconsciousness.